2011
DOI: 10.1016/j.ejphar.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The effects of nicotine, varenicline, and cytisine on schedule-controlled responding in mice: Differences in α4β2 nicotinic receptor activation

Abstract: Nicotine, varenicline, and cytisine are pharmacotherapies for tobacco dependence; the extent to which their in vivo effects vary as a function of differences in nicotinic acetylcholine receptor agonism is not clear. Male C57BL/6J mice responding under a fixed ratio 30 schedule of food delivery were used to establish the potency and time course of nicotine, varenicline, and cytisine; antagonism was examined with the non-competitive, non-selective antagonist mecamylamine and the competitive, α4β2 nicotinic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
1
23
1
Order By: Relevance
“…However, mecamylamine was less effective at blocking the small cardiovascular changes produced by cytisine. Although previous findings have reported that the in vitro and in vivo effects of cytisine were partially or fully attenuated by mecamylamine (Stolerman et al, 1983; Hall et al, 1993; Chandler and Stolerman, 1997; Cunningham and McMahon et al, 2011; Cunningham et al, 2012), the current data suggest that the large doses of cytisine used in the present study have some non-nicotinic receptor-mediated effects.…”
Section: Discussioncontrasting
confidence: 90%
“…However, mecamylamine was less effective at blocking the small cardiovascular changes produced by cytisine. Although previous findings have reported that the in vitro and in vivo effects of cytisine were partially or fully attenuated by mecamylamine (Stolerman et al, 1983; Hall et al, 1993; Chandler and Stolerman, 1997; Cunningham and McMahon et al, 2011; Cunningham et al, 2012), the current data suggest that the large doses of cytisine used in the present study have some non-nicotinic receptor-mediated effects.…”
Section: Discussioncontrasting
confidence: 90%
“…4). Overall, the actions of varenicline at low doses, as an antagonist of ␤2* nAChRs, and at higher doses, as an agonist of ␣3␤4* nAChRs as seen in the formalin test, seem consistent with varenicline's effects on body temperature, locomotion (Ortiz et al, 2012), and responding for food in mice (Cunningham and McMahon, 2011). In contrast, the agonist effects of sazetidine-A in the formalin test seems to be mediated largely by ␤2* nAChR subtypes.…”
Section: Discussionmentioning
confidence: 60%
“…The relative potency of cytisine to produce discriminative stimulus, rate-decreasing, and hypothermic effects was the same as that for all of the other nAChR agonists studied here. Moreover, mecamylamine was demonstrated previously to antagonize both the discriminative stimulus and rate-decreasing effects of cytisine (Cunningham and McMahon 2011; 2013). The mechanism responsible for the hypothermic effects of cytisine could be of some interest inasmuch as non-nicotinic mechanisms are involved in the effectiveness of cytisine as a smoking cessation aid.…”
Section: Discussionmentioning
confidence: 92%